Penerapan Ilmu Pengetahuan dan Teknologi Mesin Pengupas Kulit Ari Kedelai Jenis Screw pada Industri - Andika Wisnujati (FTI UII, 2016)
Soybeans are nutritious foods that contain lots of protein. Foods made from soy beans that are often found is tempeh. The process production tempeh in Indonesia, both in industries or traditional scale are basically similar. The difference lies in the way of peeling the cuticle soybean seeds. Peeling skin soybeans traditionally have weaknesses, among others, in terms of time this process takes a long time, and in terms of cleanliness and health of the process is very unhygienic. It is necessary to develop technologies and equipment to peeling the husk, clean and hygienic. The purpose of this study is to determine the optimum rotation soybeans the cuticle peeler and economic analysis.